2021
DOI: 10.3389/feart.2020.592659
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Plant Ashes and Their Influence on Magnetic Signatures of Fire in Soils

Abstract: Fires are an integral part of many terrestrial ecosystems and have a strong impact on soil properties. While reports of topsoil magnetic enhancement after fires vary widely, recent evidence suggests that plant ashes provide the most significant source of magnetic enhancement after burning. To investigate the magnetic properties of burnt plant material, samples of individual plant species from Iceland and Germany were cleaned and combusted at various temperatures prior to rock magnetic and geochemical character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 63 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…Till et al. (2021) also found that (for the Icelandic samples) total plant iron and saturation magnetization strongly correlated with titanium and aluminum, suggesting that inorganic materials (soil and dust) were the source of iron‐bearing magnetic phases. They conclude that vegetation ash in soil is a function of burn extent, season, chemical composition of dust and soil and plant type (Till et al., 2021).…”
Section: Speleothems As Paleofire Archivesmentioning
confidence: 95%
See 1 more Smart Citation
“…Till et al. (2021) also found that (for the Icelandic samples) total plant iron and saturation magnetization strongly correlated with titanium and aluminum, suggesting that inorganic materials (soil and dust) were the source of iron‐bearing magnetic phases. They conclude that vegetation ash in soil is a function of burn extent, season, chemical composition of dust and soil and plant type (Till et al., 2021).…”
Section: Speleothems As Paleofire Archivesmentioning
confidence: 95%
“…Magnetic enhancement noted in fire pits has previously been attributed to inputs of ferromagnetic materials from burned vegetation (McClean & Kean, 1993). More recently, experimental burning of plant samples from Iceland and Germany demonstrated that magnetic mineral concentrations increased with the extent of burning, although the amount of magnetic material did not always scale proportionally (Till et al., 2021). Till et al.…”
Section: Speleothems As Paleofire Archivesmentioning
confidence: 99%
“…These findings suggest that wildfires contribute to the magnetic enhancement of topsoil as reported elsewhere. 29,93 Understanding the impact of fires on soil magnetism is important for accurate interpretation of magnetic paleoenvironmental proxies.…”
Section: Implications For Public Health and Global Warmingmentioning
confidence: 99%
“…A recent study demonstrated the magnetic properties of plant ashes, which result from the thermal transformation of Fe in both organic and inorganic particulate matter. 29 Another study demonstrated the presence of magnetite (γ-Fe 2+ (Fe 3+ ) 2 O 4 ) and/or maghemite (γ-(Fe 3+ ) 2 O 3 ) particles in burned soils and plants characterized by spherical shapes and sizes typically between 0.1 and 2 μm. 30 The degree of pyrogenic magnetic enhancement of fire-affected soils is strongly related to the wildfire severity.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic properties are controlled by the types, size of grain, quantity, and morphology of magnetic mineral in the soil. The benefits of Fe element in the plants have also been explored among them as the controller of the photosynthesis process (Briat et al, 2010;Donnini et al, 2013;Till et al, 2021). The existence of the iron element in the soil and its relation with soil acidity properties can be described that the more acidic the soil, the smaller the iron mineral since iron dissolves in acidic substance.…”
Section: Introductionmentioning
confidence: 99%